Balance of Rights and Obligations in Governance: an Analysis of Institutional Determinants on Public Bureaucracy Performance - Sundawa Bachiar (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study is motivated by the imbalance between the rights and obligations of civil servants, which hampers bureaucratic performance and undermines public trust in local governance. The urgency lies in reforming institutions based on fairness and public accountability. The research aims to analyze the role of balancing rights and obligations as an institutional determinant of bureaucratic performance. The theoretical framework draws on organizational justice, public service motivation, and collaborative governance theories. Using a qualitative approach through an institutional case study, data were collected via in-depth interviews, participatory observation, and document analysis. The results reveal that balancing rights and obligations enhances motivation, legitimacy, and transparency through the adoption of digital administrative systems (HRIS). The study highlights the need for synergy among technology, public policy, and ethical governance to strengthen bureaucratic integrity.